A Novel Design of Multi-epitope Peptide Vaccine Against Pseudomonas aeruginosa - Esmaeilzadeh, Fatemeh; Mahmoodi, Shirin (Letters in Drug Design & Discovery, 2022)
Background: As an opportunistic pathogen, Pseudomonas aeruginosa causes many different hazardous infections. The high mortality rate resulting from infection with this antibiotic-resistant pathogen has made it a major challenge in clinical treatment; it has been listed as the most harmful bacterium to humans by the WHO. So far, no vaccine has been approved for P. aeruginosa. Objective: Infections performed by bacterial attachment and colonization with type IV pili (T4P), known as the most essential adhesive vital for adhesion, while pilQ is necessary for the biogenesis of T4P, also outer membrane proteins of a pathogen is also effective in stimulating the immune system; in this regard, pilQ, OprF, and OprI, are excellent candidate antigens for production of an effective vaccine against P. aeruginosa. Methods: In this research, various bioinformatics methods were employed in order to design a new multiepitope peptide vaccine versus P. aeruginosa. Since T CD4+ cell immunity is important in eradicating P. aeruginosa, OprF, OprI, and pilQ antigens were analyzed to determine Helper T cell Lymphocyte (HTL) epitopes by many different immunoinformatics servers. One of the receptor agonists 2 (TLR2), a segment of the Por B protein from Neisseria meningitides was used as an adjuvant in order to stimulate an effective cellular immune response, and suitable linkers were used to connect all the above mentioned parts. In the vaccine construct, linear B cell epitopes were also identified. Results: Conforming the bioinformatics forecasts, the designed vaccine possesses high antigenicity and is not allergen. Conclusion: In this regard, the designed vaccine candidate is strongly believed to possess the potential of inducing cellular and humoral immunity against P. aeruginosa.
Keywords: Linkers